Perirenalfat thickness is associated with bone turnover markers and bone mineral density in postmenopausal women with type 2 diabetes mellitus - Wang, Wei; Huang, Rong; Tang, Ping Tai; Tu, Mei; Guo, Xiu Li (Frontiers in Endocrinology, 2022)
Abstract Objective: Increasing evidences demonstrated that perirenal fat may modulate bone metabolism through several pathological pathways. This study was aimed to assess the association between perirenal fat thickness (PrFT) and bone turnover markers(BTMs), bone mineral density (BMD) in postmenopausal women with T2DM, and further exploring the correlation between PrFT and osteoporosis. Method: In this cross-sectional study, a total of 626 participants with complete data were enrolled in this study. Demographic and anthropometric information were collected. Biochemical parameters and BTMs were determined. PrFT and BMD were measured by computed tomography and dual-energy x-ray absorptiometry respectively. Correlation analysis and regression models were conducted to assess the associations between PrFT and BTMs, BMD. Multiple binomial logistic regression model was used to estimate the independent variables of PrFT for osteoporosis. Results: Overall, the prevalence of osteoporosis was 38.7%. PrFT was negatively correlated with β-cross-linked C-telopeptide of type I collagen (β-CTX ) (r= -0.216, P<0.001), L1-L4 BMD (r= -0.351, P<0.001) and T score (r= -0.396, P<0.001). PrFT also remained significantly correlated with β-CTX (β= -0.291, P<0.001), L1-L4 BMD (β= -0.109, P=0.027) and L1-L4 T score (β= -0.149, P=0.001) after adjustment for other confounding factors. Furthermore, PrFT was also independently associated with osteoporosis after adjustment for other confounding factors, the ORs(95%CI) was 1.13(1.04-1.23). PrFT was also seem to have a relative good identifying value for osteoporosis. The AUC value of PrFT in identifying osteoporosis was 0.766 (95% CI: 0.705-0.826, P<0.001). The optimal cut-off values of PrFT was 15.2 mm (sensitivity: 72.5%, specificity: 79.8%). Conclusions: PrFT was significantly associated with β-CTX, BMD and osteoporosis. These findings indicate perirenal fat may play an important role in bone metabolism.